1995
DOI: 10.1111/j.1834-7819.1995.tb03127.x
|View full text |Cite
|
Sign up to set email alerts
|

Degradative enzymes of oral streptococci

Abstract: Members of the Streptococcus sanguis group (SSG) and Streptococcus milleri group (SMG) were screened for their ability to produce glycosidase, arylamidase (peptidase), protease, dextranase and glycosyltransferase activities. Species within each group produced unique patterns of activity. The most commonly produced glycosidases were beta-D-glucosidase, beta-D-galactosidase, N-acetyl-beta-D-glucosaminidase and N-acetyl-beta-D-galactosaminidase and the least commonly produced glycosidase activity was beta-fucosid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 29 publications
1
11
1
Order By: Relevance
“…Using fluorescently labelled synthetic compounds, we demonstrated that S. australis was able to produce β-galactosidase, N-acetylglucosaminidase and N-acetylgalactosaminidase, but was unable to produce neuraminidase (Willcox et al, 1995). Demonstration of the production of β-galactosidase and N-acetylglucosaminidase with fluorescently labelled substrates was at odds with the results obtained with Rapid ID32 Strep kits, probably demonstrating the effect of different substrates.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…Using fluorescently labelled synthetic compounds, we demonstrated that S. australis was able to produce β-galactosidase, N-acetylglucosaminidase and N-acetylgalactosaminidase, but was unable to produce neuraminidase (Willcox et al, 1995). Demonstration of the production of β-galactosidase and N-acetylglucosaminidase with fluorescently labelled substrates was at odds with the results obtained with Rapid ID32 Strep kits, probably demonstrating the effect of different substrates.…”
Section: Discussioncontrasting
confidence: 47%
“…Within the S. mitis group, the species S. oralis and S. mitis are able to produce glucosyltransferases and S. mitis is able to produce fructosyltransferases. However, S. australis cannot produce either of these activities (Willcox et al, 1995) and this may be another useful distinguishing characteristic for this species.…”
Section: Discussionmentioning
confidence: 99%
“…This use of plasma proteins by oral streptococci as carbon and nitrogen sources would ostensibly benefit growth in the vegetation. Certainly, proteolytic and peptide transport systems for viridans members have been described (1,7,17,18,25,45,54), and it has been shown that small peptides can be imported into S. sanguinis, while those exceeding size limitations would require further hydrolysis by endo-and exopeptidases present on the surface or secreted by these cells (8). One such activity that facilitates these metabolic requirements, a dipeptidyl peptidase (DPP) with Gly-Pro-pNa hydrolyzing activity, has been detected in culture supernatant of S. gordonii (8,19) yet has remained undefined.…”
mentioning
confidence: 99%
“…Co., MO, USA) for plasmin like activity. 16 Substrate was dissolved in a minimum (< 20 pl) of dimethylsulphoxide (DMSO) and diluted with 50 m M N-Tris(hydroxymethy1) methyl-2-aminoethane sulphonic acid buffer (pH 7 3 , to final concentration 100 pg/mL. Substrate (100 pL) was mixed with plasmin standard (0.1 mg to 20pg/mL, Sigma Chem.…”
Section: Determination Of Tear Plasmin Levelsmentioning
confidence: 99%